2017
DOI: 10.1021/acsami.7b07996
|View full text |Cite
|
Sign up to set email alerts
|

Dual Core–Shell-Structured S@C@MnO2 Nanocomposite for Highly Stable Lithium–Sulfur Batteries

Abstract: Lithium-sulfur (Li-S) batteries have currently excited worldwide academic and industrial interest as a next-generation high-power energy storage system (EES) because of their high energy density and low cost of sulfur. However, the commercialization application is being hindered by capacity decay, mainly attributed to the polysulfide shuttle and poor conductivity of sulfur. Here, we have designed a novel dual core-shell nanostructure of S@C@MnO nanosphere hybrid as the sulfur host. The S@C@MnO nanosphere is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 68 publications
4
69
0
Order By: Relevance
“…Copyright 2018, American Chemical Society. b–d) Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Sulfur Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2018, American Chemical Society. b–d) Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Sulfur Cathodesmentioning
confidence: 99%
“…A suggested way to mitigate the low electrical conductivity of both sulfur and oxides is through the adoption of S@C@MnO 2 dual core–shell nanostructures (Figure b) . Indeed, while the outer polar MnO 2 shell is capable of chemically entrapping polysulfides, the carbon interlayer can offer high conductivity for the inner sulfur active material.…”
Section: Sulfur Cathodesmentioning
confidence: 99%
“…Also the C 1s (Figure e) spectrum demonstrates four peaks. The one at 288.1 eV is related to C═N/C═O, and those at 286.6 and 285.4 eV are attributed to C–O and C–N, respectively, whereas the peak located at 284.5 eV is indexed as C–C/C═C bond . The spectrum of the N 1s (Figure f) can be divided into three peaks at 401.3, 400.0, and 398.4 eV, which can be attributed to NH + , –NH, and –C═N, respectively …”
Section: Resultsmentioning
confidence: 96%
“…Hence, it is an effective strategy to combine functional carbon materials and metal compounds to improve the electrochemical performance of Li‐S batteries. Nevertheless, it should be emphasized that some relevant works reported that these metal compounds/carbon composites were synthesized with multiple steps, resulting in weak interaction and uneven dispersion of the metal compounds nanoparticles on the carbon surface without complete contact and protection, thus, leading to limited improvements in electrochemical performance. Besides, inclusion of inactive components like binder (PVDF) and conductivity addition (carbon black) and toxic solvent used in the slurry‐coating procedure limit the application in practical.…”
Section: Introductionmentioning
confidence: 99%